Training and Development of Teachers' Scientific Writing at SMA Negeri 1 Darul Imarah Aceh Besar: Pelatihan dan Pengembangan Karya Tulis Ilmiah Guru SMA Negeri 1 Darul Imarah Aceh Besar - Irma Zarwinda; Nurmalia Zakaria; Mulia Aria Suzanni; Safrizal Razali; Usman; Elfariyanti (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
SMA Negeri 1 Darul Imarah is one of the educational institutions in the Aceh region that focuses on vocational education. This community service aims to improve the ability of SMA Negeri 1 Darul Imarah teachers to write scientific papers through scientific writing training. Based on the results of the initial identification, it is known that only about 5% of 45 teachers have drafts of scientific papers that are ready for publication, while the majority of teachers face obstacles in writing scientific papers, such as lack of technical knowledge, free time, and access to references. The training program designed includes scientific writing techniques, utilization of reference software, and data processing with technological support. The training was attended by 20 participants and conducted in the form of a workshop, which emphasized the introduction of scientific writing structures, the use of reference managers, and writing strategies. Evaluation of the program was conducted with a pre-test and post-test, showing significant improvements in participants' motivation, confidence, and understanding of scientific writing techniques and the use of Mendeley. The evaluation results also show a decrease in barriers to scientific writing, although there are still challenges related to free time and technology facilities. Overall, the program succeeded in increasing the capacity of SMA Negeri 1 Darul Imarah teachers in preparing scientific papers, supporting their professionalism, and contributing to promotion requirements through the publication of scientific papers.